IMPLEMENTASI KEBIJAKAN PENGELOLAAN SAMPAH DI KABUPATEN KUDUS - Abdul Wachid; David Laksamana Caesar (J-KESMAS: Jurnal Kesehatan Masyarakat, 2020)
Indonesia is estimated to produce as much as 64 million tons of waste every year. This figure is very high because only 7 percent of the total destruction has been managed. Kudus Regency has a policy on waste management, but most people in Kudus Regency do not yet know the policy. This study aims to determine the implementation of waste management policies in Kudus Regency. This type of research is qualitative research, with four informants. The research instrument used an interview guide, a recording device, and a camera. The analysis method uses a thematic content analysis. Based on the results of the research, it is known that the local government has not carried out mass socialization of waste management policies to the community so that many people from various groups do not know this regulation. The implementation of waste management in the Kudus Regency is also constrained by a limited budget and waste processing equipment. In also besides, monitoring and evaluation activities are also only a formality because there is no follow-up to the monitoring and evaluation activities every year.